On the Possibility and Permissibility of Attracting Armed Forces to Resolving Intra-crisis Situations in a State - BYKOV, Andrei; GLUKHODEDOVA, Tatiana KIKOT (Journal of Advanced Research in Law and Economics, 2018)
The article deals with the issue of possibility and admissibility of involving armed forces in resolving intra-crisis situations in a state. To achieve it, dialectical, comparative-legal, statistical, system-structural methods of modeling and generalization were used. These methods made it possible to study the works of domestic and foreign scholars, regulatory and legal acts, in detail. The authors disproved the thesis of ‘inadmissibility of using the armed forces against in the citizens of the same country’. The authors note that the legislation of all developed democracies provides a very detailed coverage of the procedure for attracting and using armed forces in intra-state conflicts or other emergencies